2018
DOI: 10.1002/acr.23498
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Vessel Dilatation in Giant Cell Arteritis: A Different Subset of Disease?

Abstract: Two different subsets of LV-GCA were identified. Given the strong association between subclavian artery dilatation and aortic aneurysm, such patients should be evaluated and monitored carefully for aortic dilatation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 17 publications
0
15
0
3
Order By: Relevance
“…Differential treatment response and discrepancy of the results in each cohort may be influenced by the definition of clinical remission and relapse, prevalence of LVLs, and severity of LVLs at baseline. CRP elevation without clinical signs and symptoms was not a reliable indicator of relapse of cranial lesions and PMR [42], while clinical signs and symptoms of active GCA were not necessarily observed in patients with progression of LVLs [22,36,[43][44][45][46]. Active LVLs of GCA without clinical signs and symptoms were demonstrated by PET-CT [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Differential treatment response and discrepancy of the results in each cohort may be influenced by the definition of clinical remission and relapse, prevalence of LVLs, and severity of LVLs at baseline. CRP elevation without clinical signs and symptoms was not a reliable indicator of relapse of cranial lesions and PMR [42], while clinical signs and symptoms of active GCA were not necessarily observed in patients with progression of LVLs [22,36,[43][44][45][46]. Active LVLs of GCA without clinical signs and symptoms were demonstrated by PET-CT [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Aortic inflammation may eventually lead to the development of aortic aneurysms and dissection in patients with GCA . Little is known about the factors predictive of these late complications in GCA, although a recent study indicated that subclavian artery dilatation at diagnosis is associated with a higher risk of aortic aneurysms in GCA patients .…”
Section: Evidence For Distinct Gca Subsets Based On Clinical Featuresmentioning
confidence: 99%
“…Previous studies demonstrated that aneurysm formation slowly developed in LVLs detected at baseline by imaging (19,35,41). However, clinical signs and symptoms of active GCA were not necessarily observed in patients with progression of LVLs (19,34,(41)(42)(43)(44). Active LVLs of GCA without clinical signs and symptoms were demonstrated by PET-CT (45,46).…”
Section: Discussionmentioning
confidence: 99%